Influence of the complex of preventive measures on the timing of adaptation to removable dentures during orthopedic treatment of dental defects with the use of Ufi Gel® hard material VOCO (Germany) - Doroshenko, O.; Bida, V.; Volosovets, T.; Omelyanenko, O.; Doroshenko, M.; Gumenyuk, O. (Actual Dentistry, 2018)
Introduction. The use of partial removable dentures (CRP) in persons with dental defects restores the anatomical integrity of the tooth row, the function of chewing, aesthetics and articulation. Along with other, the most important function is to restore the function of malnutrition [1–6]. Therefore, the main task is to adapt to the ChPS with the formation of a motor stereotype, for the formation of which a complicated, but perfect interaction between the central nervous system and the motor vehicle is established. Many issues on this issue will require further study. Goal. Improvement of the effectiveness of direct orthopedic treatment of dental defects by accelerating the adaptation to orthopedic structures with the use of prophylactic measures, which consisted in rebading partial removable dentures. Material and methods of research. An electromyographic (EMG) survey was performed on 38 persons aged 45 to 60 who had been directly orthopedically treated with dentine defects with partial removable prostheses (PMP). Patients were divided into 2 groups – 1 group consisted of 18 people who made CHPP with cast acetal bases and did not undergo clinical re-banding of orthopedic constructions, and 2 group – 20 persons who were undergoing similar orthopedic intervention, but with clinical re-assembling of dentures with Ufi Gel® hard material firm «VOCO» (Germany) 1 month from the beginning of the use of removable dentures. 9 patients with intact dentition were control group. Electromyographic studies were performed with the help of a computer neuroelecgiographer M-Test produced by the association «DX-system» (Kharkiv). The bioelectric activity of chewing muscles during the EMG studies was evaluated qualitatively and quantitatively. When quantitative processing of electromyograms, the following indicators were taken into account: compression amplitude and chewing (in μV); activity time (ms); rest period (ms); the ratio of the duration of the phases of activity and rest. Results. After 3 months from the beginning of the use of removable dentures in experimental group patients, we showed a significant advantage of functional parameters and restoration of the activity of the tooth-jaw system (ZCHS) in the group where the clinical relocation of the prostheses was carried out by Ufi Gel® hard material VOCO (Germany) Conclusions: although the proposed method of increasing the efficiency of adaptation to removable prostheses is beyond doubt, it should be noted that in no case when using dentures that are removable, especially if they are manufactured immediately after the removal of the teeth, the functional parameters of the SBS are not fully recovered and do not correspond to the indicators. persons with intact dentitions, which testifies to the need for timely medical and preventive measures aimed at preserving the integrity of the toothpicks. Key words: removable dentures, direct orthopedic treatment, electromyographic indicators, material for relocating removable prostheses Ufi Gel® hard firm «VOCO» (Germany)